Application of improved A-star algorithm in fault-tolerant control of the robotic arm in the nuclear industry - Hu, Nianwei; Chen, Jinlin (Frontiers in Mechanical Engineering, 2025)
IntroductionNuclear industry robots are in high radiation environment for a long time, which leads to the robot robotic arm is prone to mechanical failure and other situations to reduce the effect of fault tolerant control of robotic arm. MethodsTherefore, the study suggests a technique of fault tolerant control of robotic arms with modified A-Star algorithm to increase the fault tolerant control effect of robotic arms under high radiation environments. The new technique plans and optimizes the robotic arm’s course using the enhanced A-Star algorithm Sliding mode control is also added to realize the fault tolerant control of robot.ResultsThe results of the study indicated that the running time of the robotic arm after using the improved A-Star algorithm was reduced by 1.92s compared with other algorithms, and the path cost was reduced by 1.46m compared with other algorithms. Moreover, the performance of the robotic arm under the improved A-Star algorithm was able to achieve 99% of the motion performance. In different environments, the deviation of the robotic arm’s movement path was reduced by 1.5m compared with other methods. The deviation angle of the robotic arm after using the sliding mode control method was only 0.04rad at the lowest level, which had a better control effect compared with other methods of sliding mode control. Finally, there was a significant improvement in the fault tolerant control of the system when using the improved A-Star algorithm and sliding mode control.DiscussionIt can be concluded that there is a significant improvement in the fault tolerant control effect of the robotic arm after using different methods. This is a good guide for the research of fault tolerant control of nuclear industrial robots.